Faith and Citizenship: A Theological Reflection on the Political Participation of Catholics - Agustinus Abraham (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Faith is often understood as a personal and spiritual relationship with God; however, in Catholic theology, faith also possesses an inherent social and political dimension. This study examines the relationship between Christian faith and citizenship through a theological reflection on the political participation of Catholics in Indonesia. The research aims to demonstrate that faith and political engagement are not separate spheres but mutually enriching dimensions of the Christian vocation to promote justice, solidarity, and the common good. Employing a qualitative method with a literature review approach, this study analyzes biblical foundations, the teachings of the Second Vatican Council, and the Church’s social doctrine, alongside contemporary discussions on political participation. The findings indicate that political participation can be understood as a concrete expression of faith and moral responsibility, particularly through civic engagement, political education, advocacy, and social involvement. Nevertheless, many Catholics remain passive due to negative perceptions of politics, corruption, and a lack of political formation. The study also highlights the importance of maintaining the Church’s moral autonomy while encouraging lay participation in practical politics. In the Indonesian context, the principle “100% Catholic, 100% Indonesian” reflects an integrated identity in which religious commitment strengthens civic responsibility. Ultimately, this research affirms that authentic faith necessarily leads to active citizenship, where Catholics contribute prophetically and ethically to the transformation of society and the realization of the common good.